MODEL PENILAIAN AUTENTIK ARAH KURIKULUM MERDEKA - Andri Irawan (STAI Sebelas April Sumedang, 2024)
The aim of writing this article is to examine and examine the authentic assessment model towards the independent curriculum. Authentic assessment as an important instrument in developing evaluation which is stated in the 2013 Education Unit Level Curriculum and Curriculum, is interesting to study and analyze as a reference in evaluating learning in the Independent Curriculum. This research is a type of literature review. In collecting data, the author took references from various journals, papers, online articles and so on from sources that are appropriate to the topic of this article. This research concludes that authentic assessment is a type of assessment carried out directly by an educator in a range of learning domains, including cognitive, affective and psychomotor, by combining process and product evaluations. This makes the implementation of the evaluation seen as more objective, real, concrete and accurate, and reflects the students' actual learning outcomes. Indicators in authentic assessment include implementation based on direct experience, authentic assessment carried out during the learning process, assessment aimed at students, continuous, integrated, and carried out with the hope that it can be used as feedback and assessment criteria. The aim of authentic assessment is to measure the results of students' competency achievement in the learning process. The principles of authentic assessment include, among others, that assessment is carried out in an integrated manner with the learning process, assessment must be carried out based on real life aspects, assessment is carried out using various measurement methods, assessment is carried out holistically. Implementing authentic assessment towards the independent curriculum is one of the important efforts made to improve student learning achievement. This authentic assessment is not only an inseparable part of the learning process, but is also one of the main pillars that greatly influences the quality of learning, both in terms of planning and implementation. In the context of the independent curriculum, there are three domains of assessment, namely diagnostic, formative and summative. Authentic assessment in the independent curriculum can be applied through performance, project and portfolio assessments.